History and Memory: Lessons from the Holocaust - Saul Friedländer (Graduate Institute Publications, 2014)
This ePaper, History and Memory: lessons from the Holocaust, presents the original text of the Leçon inaugurale delivered by Professor Saul Friedländer on 23 September 2014 at the Maison de la Paix, which marked the opening of the academic year of the Graduate Institute, Geneva. The lecture highlights an original analysis of the evolution of German memory since the end of World War II and its consequences on the writing of history. Generations of historians have been particularly marked in a...